In Situ Measurement of the Growth Rate of the (111) Face of Borax Single Crystal - Suharso Suharso (Institut Teknologi Bandung, 2005)
The quality of borax crystals is determined by grade and specifically shaped crystals of high purity. One of fundamental studies of this quality is an investigation of the growth rate of each face of borax single crystals. This paper studies the growth rates of borax single crystals along the (111) direction at various relative supersaturations using in situ optical microscopy technique to elucidate mechanism of growth and crystal growth rate equation. The result shows that the growth mechanisms of the (111) face of borax crystal at temperature of 20Â°C are spiral growth mechanism below relative supersaturation of 0.49 and a birth and spread mechanism above relative supersaturation of 0.49.